Plasma microRNA Array Analysis Identifies Overexpressed miR-19b-3p as a Biomarker of Bipolar Depression Distinguishing From Unipolar Depression - Chen, Yu; Shi, Jiabo; Liu, Haiyan; Wang, Qiang; Chen, Xiangxiang; Tang, Hao; Yan, Rui; Yao, Zhijian; Lu, Qing (Frontiers in Psychiatry, 2020)
Objectives: The clinical characteristics of bipolar disorder (current major depressive episode) (BD) overlapping with unipolar depressive disorder (UD) makes it difficult to perform an accurate diagnosis. We identified plasma miRNAs to distinguish BD from UD and to explore the relationship between miRNA expression level and clinical characteristics. Methods: Total miRNAs from blood plasma among seven UDs and seven BDs, and six controls were obtained and assayed, and the filtered miRNAs was validated in a separate group of population. The severity of depression and early life adversities were assessed. Bioinformatic analysis was conducted to investigate the involved target genesand pathways for the altered miRNAs. Results: Compared to controls, 42 miRNAs were differentially expressed in patients. miR-19b-3p, miR-3921 & miR-1180-3p were selected to validate the microarray results. Only miR-19b-3p was validated downregulated in patients. The leader predicted genes of miR-19b-3p were MAPK1, PTEN and PRKAA1. The most relevant KEGG pathways included mTOR, FoxO, and PI3-K/Akt signaling pathway. BD patients were more likely to have higher level of miR-19b-3p and more severe childhood trauma experience than UD patients. Conclusions: Peripheral miR-19b-3p might be a potential non-invasive biomarker between UD and BD, and might be involved in a pathway of inflammatory dysregulation related with early life stress.